Local Application of Strontium in a Calcium Phosphate Cement System Accelerates Healing of Soft Tissue Tendon Grafts in Anterior Cruciate Ligament Reconstruction: Experiment Using a Rabbit Model. (December 2014) - Kuang, Guan-Ming; Yau, W.P.; Lu, William W.; Chiu, K.Y.
Background: Healing of soft tissue tendon grafts within the bone tunnel in anterior cruciate ligament (ACL) reconstruction is known to be slower than that of bone–patellar tendon–bone grafts. There are attempts to accelerate healing of the graft within the bone tunnel. One of the methods is the use of strontium-enriched calcium phosphate cement (Sr-CPC). Early results in animal studies have been encouraging, although it is not known whether the accelerated healing was solely caused by the effect of strontium within the cement or by the calcium phosphate cement (CPC) itself. Hypothesis: There would be differences between Sr-CPC and conventional CPC in terms of the effect on healing of soft tissue tendon grafts within the bone tunnels in ACL reconstruction. Study Design: Controlled laboratory study. Methods: A total of 30 single-bundle ACL reconstruction procedures were performed in 15 rabbits with the use of an Achilles tendon allograft. The graft on the left limb was coated with Sr-CPC, while that on the right limb was coated with CPC. Three animals each were sacrificed for histological and histomorphometric analyses at 3, 6, 9, 12, and 24 weeks after surgery. Results: In the Sr-CPC group, early formation of Sharpey fibers was present at 6 weeks after surgery, while early remodeling of a graft-fibrocartilage-bone junction was noted at 12 weeks. In the CPC group, early formation of Sharpey fibers was only found at 9 to 12 weeks after surgery. At 24 weeks, a direct enthesis was found in both groups. According to the histomorphometric score, graft healing in the Sr-CPC group took place 3 weeks faster than that in the CPC group at and before 12 weeks; however, there was no difference between the groups at 24 weeks. Conclusion: The local application of strontium in a CPC system leads to accelerated graft healing within the bone tunnels. Clinical Relevance: The use of Sr-CPC to enhance graft-bone healing may improve the clinical results of ACL reconstruction using soft tissue tendon grafts.